Effects Of Hybridization On The Performance Of The Epoxy-Based Nanocomposites. - Chow, Wen Shyang; Chang, Lee Nah; Mohd Zulkifli, Norhamidah (2010)
Epoxy composites were prepared by hybridization of glass fiber and precipitated nano-calcium carbonate (PNCC).